Educating across cultures: Experiences of international student women in STEM - Kadriu, Ereblir; Fondaj, Rrezarta; Cahanaj, Elena (Journal of International Students, 2026)
This study explores the experiences of international female students from Kosovo and Albania pursuing undergraduate STEM degrees in the United States. The participants expressed pride in studying STEM abroad, driven by access to scholarships, top-tier resources, and mentorship. While facing obstacles such as culture shock, homesickness, language barriers, and unfamiliar teaching methods, they demonstrated resilience and determination. The study also reveals how participants view STEM education as a path to self-empowerment, professional growth, and economic mobility. Their experiences underscore the importance of institutional support systems—including inclusive practices and targeted resources—in promoting academic integration and success. This research contributes to the growing discourse on international education and gender empowerment in STEM, particularly in male-dominated fields, and highlights the societal value of fostering diversity and inclusion within global higher education.